The Impact of Stakeholder-Oriented Organisational Management Model on Organisational Performance: A Case Study of Chinese Retail Enterprises - DeKai, Fu; Munusami, Chandramalar; Nurhanan Syafiah Abdul Razak; Vikneswary Tirumalaisamy (Journal of Technology Management and Business, 2025)
This study investigates the impact of a stakeholder oriented management model on organizational performance using DL Donglai Quality, a well-known retail company in China. Based on stakeholder theory and the service profit chain model, this study analyzes the role of high employee care strategy and customer focus strategy in improving organizational performance. The study explored the mediating effect of employee care and customer oriented strategy as independent variables, organizational performance as dependent variable, and employee satisfaction and customer loyalty as mediating variables. Through an online structured questionnaire survey of 490 randomly selected employees and 533 customers, Likert scale was used for quantitative analysis, and combined with company reports and academic literature, descriptive statistics, correlation analysis, regression analysis and structural equation modeling (SEM) were applied to analyze the data. The results show that high employee care and customer-centered strategy significantly improve employee satisfaction, customer loyalty and organizational performance (p< 0.000***), and employee satisfaction and customer loyalty play a significant mediating role in this process. The research verifies the applicability of stakeholder theory and service profit chain model in the retail industry, continues the development of related theories, provides valuable empirical evidence for the global retail industry, and provides favorable support for enterprises that want to adopt stakeholder management mode, helping enterprises to achieve sustainable development.